How Digital Technology Influences Information about Fashion - Paolo Landi (ZoneModa Journal, 2022)
Fashion is experiencing the same pioneering phase as many other sectors of the economy and society. The digital age raises many questions while the crisis of understanding the "fashion phenomenon" continues to concern the sphere of the surface, thus discouraging the conceptual approach. Its pervasiveness in the media does not seem to allow problematic investigations, stopping at product information, arousing a critical reflection before it studies objective. Paolo Landi analyzes the change in information on fashion in a media universe where social networks prevail and outlines the main new elements.